2012
DOI: 10.1186/1471-2474-13-242
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of range of motion and muscle strength measurements in patients with hip osteoarthritis – an inter-rater study

Abstract: BackgroundAssessment of range of motion (ROM) and muscle strength is fundamental in the clinical diagnosis of hip osteoarthritis (OA) but reproducibility of these measurements has mostly involved clinicians from secondary care and has rarely reported agreement parameters. Therefore, the primary objective of the study was to determine the inter-rater reproducibility of ROM and muscle strength measurements. Furthermore, the reliability of the overall assessment of clinical hip OA was evaluated. Reporting is in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 39 publications
3
21
0
1
Order By: Relevance
“…As others have done, speed was set to that self‐selected by the participants and while it is agreed that individuals with OA walk slower; it is also part of the disease process. Secondly, despite studies supporting the use of passive testing to determine ROM in OA populations, passive sagittal plane range of motion can be difficult to measure in individuals with hip pathology. Research is lacking in regards to directly comparing clinical measures of ROM to motion capture methods.…”
Section: Discussionmentioning
confidence: 99%
“…As others have done, speed was set to that self‐selected by the participants and while it is agreed that individuals with OA walk slower; it is also part of the disease process. Secondly, despite studies supporting the use of passive testing to determine ROM in OA populations, passive sagittal plane range of motion can be difficult to measure in individuals with hip pathology. Research is lacking in regards to directly comparing clinical measures of ROM to motion capture methods.…”
Section: Discussionmentioning
confidence: 99%
“…Herrero et al [32] reported excellent (>0.80) intra-rater reliability and low (0.375 and 0.475) inter-rater reliability. Poulsen et al [33] found moderate inter-rater reliability for goniometric hip ROM measurement.…”
Section: Discussionmentioning
confidence: 98%
“…Mobility is measured in degrees using a standard (30 cm) goniometer [40]. Inter-tester reliability (r = 0.98; ICC = 0.99) and validity (r = 0.97; ICC = 0.98) of goniometer measurements of knee joint motion have been shown [41].…”
Section: Methodsmentioning
confidence: 99%